Edukasi dan Pengelolaan Gaya Hidup Penyakit Sindrom Metabolik Pada Lansia di Kecamatan Pedurungan, Semarang - Januarti, Ika Buana; Maharyani, Airina; Anggraini, Monica Putri (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM Universitas Respati Indonesia), 2025)
Metabolic syndrome has an incidence rate of 25%. This disease has symptoms such as patients having an above-normal waist circumference ≥90 cm for males and ≥80 cm for females, hypertriglyceridemia, low HDL cholesterol levels, hypertension, and diabetes mellitus. Unhealthy lifestyle factors, such as a diet high in fat and sugar and a lack of physical activity, play an important role in the emergence of metabolic syndrome. This community service activity aims to increase public knowledge, especially among the elderly, about metabolic syndrome and healthy lifestyle management as a preventive measure. Education was conducted using lectures followed by interactive discussions. The effectiveness of the activity was measured by comparing pre-test and post-test results to assess participants' knowledge improvement. The activity was attended by 32 participants from RT 09, Pedurungan District, Semarang City. The evaluation results showed a 12% increase in knowledge afterthe education, with a good improvement category. Statistical analysis using the Paired Sample T-Test showed a significant difference between the pre-test and post-test scores with a significance value of 0.004 (p < 0.05). These findings indicate that the educational activity had a significant effect on increasing the community's knowledge about metabolic syndrome and the importance of adopting a healthy lifestyle.